ANALISIS PERAMALAN PERMINTAAN BENSIN PERTAMAX MENGGUNAKAN METODE TIME-SERIES FORECAST PADA PT. ZINDAN UTAMA JAYA PADA TAHUN 2024 - Muhammad Zindan Taufikurrahman; Ria Arifianti; Raden Marsha Aulia Hakim (POLITEKNIK LP3I JAKARTA, 2024)
Gas Station PT. Zindan Utama Jaya is a company engaged in the marketing of fuel and gas located in Cirebon City. This study aims to enable the company to see the prediction of the amount of fuel demand in the next period so that the company can prepare fuel stock in this case Pertamax fuel, and the company can also prepare future marketing strategies seen from the forecast results. The research method used is quantitative with a time-series method that uses historical data on gasoline sales at PT. Zindan Utama Jaya for one year as the main data and its implementation with the dimensions of time series, behavior of demand, and causes of demand behavior. In its calculations, this study uses the moving average method, exponential smoothing, and adjusted exponential smoothing with error calculations using MAD, MSE, and MAPE. The results of this study indicate that the most effective calculation method calculated from the smallest error is the exponential smoothing method with α = 0.1.